’n Vergelyking van Calvyn se 1545-Kategismus en die Heidelbergse Kategismus oor die Onse Vadergebed - Coetzee, C. F. C. (Koers, 2009)
A comparison between Calvin’s Catechism of 1545 and the Heidelberg Catechism on their exposition of the Lord’s Prayer Several studies on the relationship between Calvin’s Catechism (1545) and the Heidelberg Catechism have already been conducted. However, the need for a study of a comparison between the two catechisms on the Lord’s Prayer was emphasised at the South African Calvin Research Conference in 2004. In the sixteenth century Reformation the Lord’s Prayer was a subject of considerable importance. Calvin wrote no less than eight different expositions of the Lord’s Prayer in his commentaries, catechisms of 1538 and 1545 and the different editions of his “Institutes”. In both the Geneva Catechism of 1542/1545 and the Heidelberg Catechism the exposition of the Lord’s Prayer forms an important part. A comparison of these expositions leads to the conclusion that the theological insights of John Calvin played a major role in the formulation of the Heidelberg Catechism. The Heidelberg Catechism is part of our Calvinist heritage and should still be used in the instruction of our children and confessed as our true and living faith.